Action-centred design to find opportunities in times of multiple crises : Designing a toolkit from a participatory conference - Fuad-Luke, Alastair; Yavuz, Seçil Uğur; Sy, Corinna; Schubert, Jennifer; Krois, Kris (My University, 2020)
The global crisis around the COVID-19 pandemic raises questions about our societal conditions while amplifying the challenges of our existing multiple crises to wider questions of sustainability. Such crises, which are both threat and opportunity, have been highlighted for 50 years within the design domain which has re-orientated towards ideas of ecological, social and economic transition and transformation. Against this background, a 7-year old conference series, presciently called By Design or By Disaster, had to convert to an online format during the COVID-19 lockdown in Italy. Applying eco-social and participatory design principles the participants of the conference, Beyond Crisis, co-created 21 parallel workshops tasked with the aim of each generating three actions on diverse topics reflecting the interests of the participants. Live reports and synthesis of the actions generated a broad mapping of the situation to help build a spirit and momentum for social-ecological transformation through design. Subsequent analysis of the content of the workshops and actions led to the development of a prototype opensource toolkit, the Toolkit for Designing Actions in Times of Multiple Crisis, that facilitates the creation of action plans with multiple actors. This toolkit for action-centred design has the potential to help diverse actors deal with multiple crises while simultaneously helping reconfigure our societal and human to other-than-human relations by materialising preferable rather than probable or possible futures.
Keywords: Action-centred design; Diverse actors; Multiple crises; Toolkit; Transition; Social-ecological; Transformation